Research progress of biomass energy conversion technology and application in China - Yitong Niu (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
With the rapid development of the people's economy, the consumption of various energy sources is increasing. The increasing consumption of non-renewable energy sources can lead to increased sources of air pollution. In addition, energy sources from fossils if used continuously can run out. To overcome this problem, renewable energy sources are created to replace fossil fuels. As a renewable energy source that can replace fossil fuels, biomass is currently receiving a lot of attention from countries around the world and is increasingly being used. Biomass can be produced from animal waste or manure that is put in a reactor tube. In this paper, we focus on the technology of converting biomass to energy and describe the application of biomass to energy to implement efficient application of biomass to energy.